ANALISIS DIAMOND FRAUD THEORY DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN Studi Kasus Pada Industri Keuangan Dan Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ignasius Narew; Dianah Zuhroh; Harmono Harmono (Jurnal Akuntansi Trisakti, 2021)
Fraud is a threat to an entity and is a problem that continues to this day. Thus the purpose of this study is to examine the effect of variables from elements of the diamond fraud theory which include financial stability, external pressure, financial targets, personal financial needs, number of audit committee members, nature of industry, auditor turnover, and auditor turnover on fraudulent financial statement of financial and manufacturing industry companies listed on the Indonesia Stock Exchange. The samples used in this study were 67 financial industry companies and 67 manufacturing industrial companies in the 2014-2019 period. The data were analyzed using logistic regression because the fraudulent financial statement variable in this study is a dummy variable whose determination is based on the calculation of the Altman Z Score. The findings of this study indicate that of the 8 elements of the diamond fraud theory variable, only external pressure and financial target variables have an effect on fraudulent financial statements in financial industry companies, while in the manufacturing industry only external pressure and nature of industry variables have a significant effect.  Keywords :diamond fraud theory, fraudulent financial statement, financial stability, personal financial need, number of audit committee members, nature of industry, change of auditors, and change of directors